Effects of Substrate Temperature on the Properties of Indium Nitride Thin Films Grown on Flexible Prepared by Reactive Sputtering Method - Osman, Siti Aisyah; Lee, Zhi Yin; Fong, Chee Yong; Ng, Sha Shiong (2015)
In this study, indium nitride (InN) thin films were deposited on kapton polymide flexible substrate by reactive radio frequency (RF) sputtering method using indium target in a mixture of Ar and N2 gases. The InN thin films were deposited under different substrate temperatures, i.e., 1 00°C and 200°C. The effects of substrate temperature on structural, surface morphologies and optical properties of InN thin films were systematically investigated by using X-ray diffraction technique, field emission scanning electron microscope, energy dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy.